Inflammatory Markers and Gait Speed Decline in Older Adults - Verghese, Joe (Oxford University Press, 2011)
BACKGROUND. Increased inflammatory activity and gait speed decline are common with aging, but the association between the two is not well established. The objective of this study was to determine the influence of inflammatory markers, interleukin-6 (IL-6), and tumor necrosis factor alpha, on gait speed performance and decline in older adults. METHODS. We conducted cross-sectional and longitudinal analyses of 333 adults aged 70 and older (61% women) with gait and biomarker assessments identified from participants in the Einstein Aging Study, a community-based aging study. Gait velocity measured at baseline and annual follow-up visits (median follow-up 2.3 years) was the main outcome. RESULTS. At baseline, higher interleukin-6 levels were associated with slower gait velocity (estimate −4.90 cm/s, p = .008). Adjusted for age, gender, education, and medical illnesses, a one-unit increase in baseline log IL-6 levels was associated with a 0.98 cm/s faster gait speed decline per year (p = .002). The results remained significant after adjustments for additional potential confounders such as physical activity levels, body mass index, and medications. Participants in the highest IL-6 quartile had a 1.75 cm/s/year faster decline in gait velocity compared with those in the lowest quartile (p = .002). Tumor necrosis factor alpha was not associated with gait velocity at cross-section or with gait speed decline. CONCLUSIONS. IL-6 levels are associated with gait performance in community residing seniors and predicts risk of gait speed decline in aging.